Used Materials Media for Improving Fine Motor Skills in Early Childhood: Media Bahan Bekas untuk Meningkatkan Keterampilan Motorik Halus pada Anak Usia Dini - Maspupah; Fitriah; Mastikawati; Amiroh; Azwir (Indonesian Journal of Education Methods Development, 2024)
General Background: Early childhood education emphasizes the development of fine motor skills as a foundation for later learning readiness. Specific Background: However, limited variation in learning media often restricts children’s opportunities to practice fine motor coordination, creativity, and environmental awareness. Knowledge Gap: Few studies have systematically examined the role of recycled or used materials as a sustainable medium for improving fine motor development in early childhood education. Aim: This study investigates the use of used materials to strengthen cutting and pasting skills of children aged 4–5 years in PAUD An-Nur Tanjung Jabung Timur. Results: Using classroom action research in two cycles with 10 participants, findings show significant improvement: in cutting, 70% reached the “Very Well Developed” category, while in pasting, 80% achieved this category by the second cycle. Novelty: The research highlights how simple, accessible, and environmentally friendly materials can serve as effective media for structured fine motor practice. Implications: The findings suggest the integration of used materials in PAUD learning not only enhances motor skills but also fosters creativity and ecological responsibility. Highlights: Fine motor skills of young children improved significantly through used materials. Recycled media fostered creativity and environmental awareness. The study offers sustainable strategies for PAUD motor development. Keywords: Fine Motor Skills, Recycled Materials, PAUD, Early Childhood, Creativity